Multinationals, tax holidays, and technology transfer - Kaz Miyagiwa; Yuka Ohno (Osaka University, Institute of Social and Economic Research (ISER), 2008)
Host country governments often grant investment incentives to foreign firms locating in their territories. We show that such preferential treatment of foreign firms can facilitate transfer of foreign technology, induce entry by the local firm, and increase host country welfare. However, this pro-competitive result occurs when preferential treatment is granted for a limited time; i.e., it takes the form of tax holidays, and is absent under permanent tax concessions.
Keywords: F1; O3; 330; Tax holidays; Free trade zones; Foreign direct investment; Technology transfer; Multinational firms; Multinationales Unternehmen; Investitionspolitik; Steuervergünstigung; Technologietransfer; Theorie